MO572: Effects of Ketoanalogues on the Evolution of Bone Mineral Metabolism in Patients With Advanced Chronic Kidney Disease. (3rd May 2022) - Kosmadakis, Georgios; Isnard Rouchon, Myriam; Fuentes, Fanny; Ramade, Nathalie; Baudenon, Julien; Deville, Clemence; Enache, Ioana; Gueret, Claudine; Haskour, Abraham; Necoara, Aura; Rance, Nicole
Abstract: BACKGROUND AND AIMS: There is a mounting volume of evidence on the efficacy of ketoanalogues associated with low protein diets, concerning the nephroprotective effects in patients with advanced chronic kidney disease (CKD). The important number of capsules daily ingested associated with their important calcium content would potentially affect the bone mineral metabolism of this group of patients. The aim of this study is to investigate the effects of ketoanalogues on the evolution of the bone mineral metabolism parameters in patients with advanced CKD. METHOD: This is a prospective non-randomized controlled comparative study of two groups of patients. The results are shown as mean ± ESM. The first group (intervention) (20 patients, 12/8 M/F, mean age 71.9 ± 2.9, 10 with diabetes) was treated with ketoanalogues associated with a low protein diet and the control group (17 patients, 9/8 M/F, mean age 68.2 ± 3.3, 8 with diabetes) had a conventional follow-up of CKD. We studied the evolution of the body weight, renal function (glomerular filtration rate measured by the CKD-EPI formula in mL/min/1.73 m 2 ), 24 h proteinuria, salt and protein consumption, serum albumin, serum prealbumin, alkaline reserve, serum phosphate levels, serum parathormone levels and calcium levels corrected for serum albumin at baseline as well as 6, 12 and 24 months post-inclusion. We performed a T -test for independent groups in order to study the differences between the two groups in every time point of the study. P-values < 0.05 were considered statistically significant. RESULTS: The results are shown in the Table 1 . There were no differences between the two groups at baseline. There was a significant nephroprotective effect of the ketoanalogues after 12 and 24 months. Alkaline reserve and serum calcium levels were significantly higher in the intervention group after 6, 12 and 24 months. Serum phosphate and serum parathormone levels were significantly higher in the control group 6 months, 1 and 2 years after the baseline. All patients were treated with the appropriate agents for the correction of the perturbed study parameters. During the 2-year follow-up, four patients from the study group (two pre-emptive renal transplantations, one death from oncologic causes and one start of dialysis) and eight patients from the control group (three deaths and five dialysis initiations) quitted the study. CONCLUSION: In conclusion, the treatment with ketoanalogues and low protein diet has a significantly positive impact on the bone mineral metabolism of the patients with advanced CKD. It is unknown whether this is due to the high calcium content of the capsules or from the fact that the renal function is better preserved in the intervention group